2021
DOI: 10.3390/genes12101524
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Satellite III (1q12) Copy Number Variation in the Adaptive Response during Aging, Stress, and Pathology: A Pendulum Model

Abstract: The pericentric satellite III (SatIII or Sat3) and II tandem repeats recently appeared to be transcribed under stress conditions, and the transcripts were shown to play an essential role in the universal stress response. In this paper, we review the role of human-specific SatIII copy number variation (CNV) in normal stress response, aging and pathology, with a focus on 1q12 loci. We postulate a close link between transcription of SatII/III repeats and their CNV. The accrued body of data suggests a hypothetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 145 publications
(188 reference statements)
2
21
0
Order By: Relevance
“…After the release of the stress and the restoration period during the post-examinational vacations, the SatIII content normalized, presumably being reduced by a hypothetical reverse mechanism that counterbalances the satellite repeat expansion [ 90 ]. These findings became a validation of the “pendulum model” published earlier [ 85 ].…”
Section: Psychoemotional (Affective) Stress-induced Changes In the Ab...supporting
confidence: 67%
See 2 more Smart Citations
“…After the release of the stress and the restoration period during the post-examinational vacations, the SatIII content normalized, presumably being reduced by a hypothetical reverse mechanism that counterbalances the satellite repeat expansion [ 90 ]. These findings became a validation of the “pendulum model” published earlier [ 85 ].…”
Section: Psychoemotional (Affective) Stress-induced Changes In the Ab...supporting
confidence: 67%
“…When patients who experienced fetal hypoxia were isolated from the large common sample of schizophrenia patients, this sub-group appeared to contain the same amounts of SatIII DNA in their genomes as healthy controls ( p > 0.2) [ 76 ]. The idea of two reverse processes of satellite copy gain/reduction under stress conditions was embodied in a model called the “pendulum model” [ 85 ].…”
Section: The Role Of Satellite Repeat Abundance In Modulating Stress ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Intron retention prevents the export of the pre-mRNAs from the nucleus, resulting in a suppression of gene expression at the posttranscriptional level. It was reported that satellite III and satellite II exhibit copy number variation (CNV) during the stress response, aging and pathology, and a close link between their transcription and CNV is postulated [ 77 ].…”
Section: Satellite Dna In Stress Responsementioning
confidence: 99%
“…Given the well-known connections between genome instability and human satDNAs (Balzano et al 2021), it would be reasonable to expect HSAT1 copy number variation (CNV) to differ between normal and tumor cell lines. Nonetheless, the polymorphic nature of these sequences (greatly varying even between individual arrays) and their natural behavior as sources of CNV in genome evolution (Warburton et al 2008; Black and Giunta 2018; Lower et al 2018; Porokhovnik et al 2021), limit any assessment of HSAT1 CNV contribution to instability in the absence of information about the starting point. In fact, satellite CNV is often so substantial that it is cytogenetically detectable between individuals (Miga 2019).…”
Section: Resultsmentioning
confidence: 99%